SARS-CoV-2 RT-PCR positivity in relation to clinical and demographic characteristics in residents of border quarantine centres, Khyber Pakhtunkhwa, Pakistan: a prospective cohort study. (20th June 2022) - Imran, Muhammad; Uddin, Azhar; Ambade, Preshit; Khan, Sajjad; Wahab, Abdul; Akbar, Hussain; Iqbal, Zafar; Ernst, Kacey
Abstract: Background: As international travellers were the primary source of sever acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, border checkpoints became an important tool to isolate cases. We determined the period prevalence and SARS-CoV-2 reverse transcription polymerase chain reaction positivity in relation to clinical and demographic characteristics in healthy travellers quarantined at the Pakistan–Afghanistan border. Methods: The study was conducted from 15 to 25 April 2020. Period prevalence was calculated and the association between positivity and individuals' age, sex and occupation were assessed using χ 2 and Mantel–Haenszel tests. Logistic regression was used to calculate adjusted odds ratios (ORs) for each age group. Time-to-event (TTE) analysis was conducted to check the difference in positivity among various groups. Results: In a total of 708 individuals, 71 tested positive (10%). Compared with those ≤20 y of age, the sex- and occupation-adjusted odds of testing positive were less among the older age group (41–60 y; OR 0.26, p=0.008). Taxi drivers had higher odds of testing positive (OR 4.08, p<0.001). Kaplan–Meier curves and hazard ratios (0.32, p<0.01) showed that the positivity period differed significantly across the pre-symptomatic vs asymptomatic group (26 vs 14 d). Conclusions: The cases who were likely to acquire infection through occupational exposure largely remained asymptomatic. For effective control of transmission and the emergence of new variants, testing capacities should be revamped with effective isolation measures.